Near infrared emitting molecular rotor based on merocyanine for probing the viscosity of cellular lipid environments. (21st January 2021) - Mukherjee, Tarushyam; Martinez-Sanchez, Ramon J.; Fam, Kyong T.; Bou, Sophie; Richert, Ludovic; Garnier, Delphine; Mély, Yves; Kanvah, Sriram; Klymchenko, Andrey S.; Collot, Mayeul
Abstract : We synthesized and characterized the photophysical properties of new non-charged merocyanines. Among them, MC-TB was shown to be a bright and efficient fluorogenic molecular rotor able to probe the viscosity of lipid droplets and mitochondria. Abstract : Fluorogenic molecular rotors have demonstrated their efficiency to probe viscous environments in various cell compartments. Green emitting BODIPY rotors are non-charged and thus are widely used in bioimaging. However, non-charged rotors operating in the near infrared region and exhibiting high brightness are rare. We herein synthesized five different merocyanines dyes (MCs) from a dihydro-xanthene scaffold and studied their spectroscopic properties. Notable differences were observed, which allowed us to establish structure–properties relationships. Among MCs, MC-TB, bearing a thiobarbituric electron acceptor group, displayed high sensitivity to viscosity, excellent photostability, high extinction coefficient (>100 000 M −1 cm −1 ) and bright emission with sharp peaks in the near infrared region (∼700 nm), which are favorable features for bioimaging. In cells, MC-TB stained the most hydrophobic and viscous organelles, namely the lipid droplets. To increase the versatility of this new rotor, a mitochondria targeted version, MC-TB-Mito, was synthesized. The latter showed similar appealing photophysical properties and it was successfully used to report variation and heterogeneity of mitochondrial viscosity using multicolor fluorescence microscopy and fluorescence lifetime imaging (FLIM). Finally, we used MC-TB-Mito to reveal an important increase of mitochondrial viscosity during cell apoptosis.